Makelar Kasus dalam Kajian Filosofis Normatif Hukum Islam - Abdulahanaa Abdulahanaa (Al-Manahij: Jurnal Kajian Hukum Islam, 2016)
Case broker essentially reflects intervention of an administrative process of law enforcement. Thus, based the facts, case broker is already identified as an employment with proscribed income. The problem is on the one hand case broker is already connoted as a illegitimate job, on the other hand the existence of case brokers become "necessities" that cannot be circumvented. Therefore, it is necessary to study the normative philosophical foundation of case broker in Islamic law. The legal basis of case broker can be referred to Usul al-Fiqh by using the method ofmaşlahah almursalah, then it is adopted operationally by using ijarah method of 'aqd (agreement). In particular, there is no specific rule(proposition) found in the Qur'an and Prophetic traditions regarding case brokers.But, in general, the argumentsderived from the principles of Islamic economic law (muamalah), especially with regard to ijarah, deductively can be used as legal basis of case broker. The essence of case broker in normative philosophical perspective is a job that can be justified with regard to the concept and rules of seeking livelihood through ijarah contract (worker hiring). Therefore, a case broker is permissible (halal) receiving fees for services (ujrah) from his client agreed by both parties as long as all adhere to the rules that apply in ijarah law.